Improving Environmental Literacy Through Primary Education: Preparing Students as Environmental Advocates - Ainin, Dewi Tumatul; Asafri, Helty (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
Primary education plays a crucial role in shaping students’ awareness and commitment to the environment. This paper aims to examine the importance of primary education in enhancing environmental literacy and preparing students as environmental advocates. Through a literature review, this research explains the concept of environmental literacy and its positive impact on environmental sustainability. Furthermore, strategies and approaches that can be used in primary education to enhance students’ environmental literacy are discussed. These include integrating environmental issues into the curriculum, developing critical thinking skills, providing practical experiences in real-world environments, and engaging students in environmental action. Additionally, the application of technology in environmental education is also explored as an innovative tool that can enhance learning and student participation. The paper also discusses the challenges and opportunities that may arise in implementing environmental education at the primary level. This research can contribute to developing a comprehensive approach in primary education that integrates environmental issues throughout the curriculum and school activities. This approach involves cross-disciplinary teaching, practical experiences in the real environment, the development of critical thinking skills, and collaboration with stakeholders. It is hoped that collaborative efforts among schools, teachers, parents, and the community will strengthen primary education as a primary foundation for enhancing students’ environmental literacy and shaping a generation that cares for the environment.